Ultrasonic Imaging of the Onset and Growth of Fractures Within Partially Saturated Whitby Mudstone Using Coda Wave Decorrelation Inversion. Issue 7 (11th July 2020) - Zotz‐Wilson, Reuben; Douma, Lisanne A. N. R.; Sarout, Joel; Dautriat, Jeremie; Dewhurst, David; Barnhoorn, Auke
Abstract: Using active ultrasonic source survey data, coda wave decorrelation (CWD) time‐lapse imaging during the triaxial compression of Whitby Mudstone cores provides a 3‐D description of the evolution and redistribution of inelastic strain concentrations. Acoustic emissions (AEs) monitoring is also performed between any two consecutive surveys. From these data, we investigate the impact of initial water saturation S w on the onset, growth, and reactivation of inelastic deformation, compared to the postdeformation fracture network extracted from X‐ray tomography scans. Our results indicate for the applied strain rate and degree of initial water saturation, and within the frequency range of our ultrasonic transducers (0.1 to 1 MHz), that inelastic strain localization and propagation in the Whitby Mudstone does not radiate AEs of sufficient magnitude to be detected above the average noise level. This is true for both the initial onset of inelasticity (strain localization) and during macroscopic failure. In contrast, the CWD results indicate the onset of what is interpreted as localized regions of inelastic strain at less than 50% of the peak differential stress the Whitby Mudstone can sustain. The seemingly aseismic nature of these clay‐rich rocks suggests the gradual development of inelastic strain, from the microscopic diffuse damage, up until the macroscopic shear failure. Key Points: Inversion of coda wave decorrelationdata allows the imaging of subwavelength strain localization CWD inversion is capable of imagingaseismic triaxial deformation and failure of the Whitby mudstone Onset of aseismic precursory strain is imaged at less than 42% of peak differential stress